Rotating MHD flow of a generalized burgers' fluid over an oscillating plate embedded in a porous medium - Khan, Ilyas (Vinca Inst Nuclear Sci, 2015)
The present paper is concerned with the magnetohydrodynamic unsteady rotating flows of generalized Burgers' fluid with a porous medium. The flows are created by the plate oscillations. Modified Darcy's law has been employed to model the governing problem. Closed-form solutions corresponding to cosine and sine oscillations are obtained by the Laplace transform method. The performed calculations disclose that Hartmann number, porosity of the medium, angular frequency, and oscillating frequency have strong influence on the velocity. The graphs are presented for such influence and examined carefully.